Sudan ebolavirus long recovered survivors produce GP-specific Abs that are of the IgG1 subclass and preferentially bind FcγRI - Olga Radinsky (Nature Portfolio, 2017)
Abstract Ebolavirus is a highly lethal pathogen, causing a severe hemorrhagic disease with a high fatality rate. To better understand immune correlates of protection by virus specific IgG, we investigated the evolution of the Fcγ receptors (FcγRs)-activating capabilities of antiviral IgG in serum samples of long recovered survivors. To this end, longitudinal serum samples from survivors of Sudan ebolavirus (SUDV) infection, studied over years, were examined for the presence of Ebola-GP specific IgG subclasses, and for their binding to FcγRs. We developed a cell-based reporter system to quantitate pathogen-specific antibody binding to FcγRIIIA, FcγRIIA, FcγRIIB and FcγRI. With this system, we demonstrate that anti-GP-specific stimulation of the FcγRI reporter by survivors’ sera was substantially high one year after acute infection, with a slight reduction in activity over a decade post infection. We further demonstrate that GP-specific IgG1 is by far the seroprevalent subclass that retained and even enhanced its presence in the sera, over ten years post infection; the prevalence of other GP-specific IgG subclasses was considerably reduced over time. In accordance, GP-specific FcγRI reporter response and GP-specific total IgG1 subclass correlated in the studied group of Ebola survivors. These observations are important for further informing Ebola vaccine and therapeutic development.